Evaluating the Effect of Cardiac Rehabilitation Care Plan on Quality of Life of Patients Undergoing Coronary Artery Bypass Graft Surgery - Masoumi, Seyedeh Zahra; kazemi, farideh; Khani, Somayeh; Seifpanahi-Shabani, Hazhir; Garousian, Maryam; Ghabeshi, Mehran; Razmara, Fatemeh; Roshanaei, Ghodratollah (International Journal of Cardiovascular Practice, 2017)
Introduction: Cardiovascular surgeries are among the conventional surgeries aimed at increasing the survival rate and improving the quality of life of patients. This study aimed to evaluate the effect of cardiac rehabilitation on quality of life of patients undergoing Coronary artery bypass graft (CABG) surgery.Methods: This was a semi-experimental study performed on 160 patients undergoing CABG surgery. The rehabilitation program was carried out for 13 weeks (three sessions per week) in 40 sessions, six weeks after the CABG surgery. The MacNew standard questionnaire and the general health questionnaire (S-f 36) were completed before the beginning of rehabilitation sessions as well as after completion of these sessions by patients.Results: According to the results, the quality of life of patients significantly increased in the physical and emotional areas after the rehabilitation program. The results also indicated that there was a significant difference between various levels of research in the physical functioning variables, dysfunction due to physical health, dysfunction due to emotional health, energy/fatigue of individuals, emotional well-being, social functioning, pain, and general health.Conclusions: The present results indicated the improved quality of life of patients in all the areas after cardiac rehabilitation intervention, compared to before that. Therefore, paying more attention to cardiac rehabilitation is necessary due to its positive effects on increasing the quality of life of patients.